Capital Punishment and Deterrence: Some Further Thoughts and Additional Evidence - Ehrlich, Isaac (Journal of Political Economy, 1977)
Investigation of the deterrent effect of capital punishment has implications far beyond the propriety of execution as punishment since it concerns the general question of offenders' responsiveness to incentives. This study challenges popular allegations by earlier researchers denying the deterrence hypothesis. The empirical analysis based on cross-sectional data from the U.S. corroborates my earlier analysis of the time series. Findings indicate a substantial deterrent effect of punishment on murder and related violent crimes and support the economic and econometric models used in investigations of other crimes. Distinctions between classes of executing and nonexecuting states are also examined in light of theory and evidence.